The Role of Exercise on Sleep Quality: An Observational Study in the Medical Student Community in Jakarta, Indonesia - Muhammad Naufal Razaan; Lontoh, Susy Olivia (Community Medicine and Education Journal, 2024)
Optimal sleep quality is very important for the health and academic performance of medical students. However, high academic demands often cause lack of sleep and sleep disorders. Exercise has been shown to have a positive effect on sleep quality in the general population, but research on the role of exercise on sleep quality in medical students is still limited. This study aims to identify the relationship between the level of physical activity (exercise) and sleep quality among medical students in Jakarta. This cross-sectional observational study involved 350 medical students from various universities in Jakarta. Physical activity data was collected using the International Physical Activity Questionnaire (IPAQ), while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Logistic regression analysis was used to identify the relationship between physical activity and sleep quality, by controlling for confounding variables such as age, gender and stress level. The results showed that medical students who were physically active had a lower risk of experiencing sleep disorders compared to students who were less active. Logistic regression analysis showed that moderate to vigorous physical activity was significantly associated with better sleep quality (OR = 0.56; 95% CI: 0.35-0.88; p = 0.012). Exercise has an important role in improving sleep quality in medical students. Exercise-based interventions may be an effective strategy to address sleep problems in this population.